Willingness to use a rapid diagnostic test for malaria in a rural area of central Côte d'Ivoire - Comoé Colombe Coffie; Ouattara Allassane F; Raso Giovanna; Tanner Marcel; Utzinger Jürg; Koudou Benjamin G (BMC, 2012)
Abstract Background Malaria mortality is mainly a direct consequence of inadequate and/or delayed diagnosis and case management. Some important control interventions (e.g. long-lasting insecticidal nests) have contributed to reduce malaria morbidity and mortality in different parts of the world. Moreover, the development and effective use of rapid diagnostic tests (RDTs) hold promise to further enhance the control and elimination of malaria, particularly in areas where health services are deficient. The aim of this study was to determine knowledge, attitudes, practices and beliefs in relation to RDTs for malaria in rural Côte d'Ivoire. Methods One hundred individuals from Bozi and Yoho who sought care at the health centre in Bozi and were offered an RDT for malaria were interviewed in April 2010 using a pre-tested questionnaire on practice and perceptions in relation to RDTs for malaria. The relationships between acceptance of RDTs and factors related to opinions were identified, using generalized linear mixed models. Qualitative data from open-ended questions complemented the quantitative analysis. Results Only 34 out of 100 patients who were offered an RDT for malaria were willing to undergo the test. People who perceived blood as a sacred body fluid were less likely to comply with an RDT. The concurrent availability and use of RDTs for HIV and malaria was associated with an unwilling attitude towards RDTs for malaria (Fisher's exact test, p <0.001). The initial willingness of patients to accept malaria testing with RDTs was significantly related to general fear and wanting to know malaria infection status. For further and regular use of RDTs, a strong relationship was observed between acceptance and the idea that an RDT is a pretext used by health worker to know HIV status (odds ratio (OR) = 16.61, 95% confidence interval (CI) = 1.03-268.5). Those thinking that blood samples were useful for medical diagnoses were 8.31-times (95% CI = 2.22-31.1) more likely to undergo an RDT compared to those rejecting blood sampling as a diagnostic strategy. Conclusion Socio-cultural factors might be barriers for accepting RDTs in general health services. There are social representations of malaria and HIV/AIDS, symbolic for blood or experiences in relation to blood taking and blood-related diseases in relation to the introduction and routine use of RDTs. Special attention should be given to these barriers as otherwise the promotion of RDTs for prompt and effective diagnosis and subsequent management of malaria is hampered.